Nearest Level Control for a Three-Phase to Single-Phase Modular Multilevel Converter for Solid State Transformers - Rojas-Lobos, F; Diaz-Diaz, M; Arancibia-Gonzalez, D; Droguett-Olea, G; Uriarte-Gonzalez, M (Institute of Electrical and Electronics Engineers Inc., 2018)
The three-phase to medium frequency single-phase direct conversion with the Modular Multilevel Converter for Solid State Transformers involves control and modulation challenges due to the switching devices limitations. The use of Nearest Level Control (NLC) as a modulation technique to properly synthesize medium frequency voltages at the output is proposed on this paper, paying special attention to the arm inductors effect at medium frequency operation. Using NLC results in low distortion medium voltage and medium frequency single-phase output, achieving good controllability and reaffirming the suitability of the converter for its application in Solid State Transformers. © 2018 IEEE.
Keywords: M2C; modular Multilevel Converter; nearest Level Control; NLC; solid State Transformers